Metabolic regulation of forkhead box P3 alternative splicing isoforms and their impact on health and disease - Zhidan Luo; Zhidan Luo; Yihua Zhang; Qais Waleed Saleh; Qais Waleed Saleh; Jie Zhang; Zhiming Zhu; Martin Tepel; Martin Tepel (Frontiers in Immunology, 2023)
Forkhead Box P3 (FOXP3) is crucial for the development and suppressive function of human regulatory T cells (Tregs). There are two predominant FOXP3 splicing isoforms in healthy humans, the full-length isoform and the isoform lacking exon 2, with different functions and regulation mechanisms. FOXP3 splicing isoforms show distinct abilities in the cofactor interaction and the nuclear translocation, resulting in different effects on the differentiation, cytokine secretion, suppressive function, linage stability, and environmental adaptation of Tregs. The balance of FOXP3 splicing isoforms is related to autoimmune diseases, inflammatory diseases, and cancers. In response to environmental challenges, FOXP3 transcription and splicing can be finely regulated by T cell antigen receptor stimulation, glycolysis, fatty acid oxidation, and reactive oxygen species, with various signaling pathways involved. Strategies targeting energy metabolism and FOXP3 splicing isoforms in Tregs may provide potential new approaches for the treatment of autoimmune diseases, inflammatory diseases, and cancers. In this review, we summarize recent discoveries about the FOXP3 splicing isoforms and address the metabolic regulation and specific functions of FOXP3 splicing isoforms in Tregs.